2012
DOI: 10.18584/iipj.2012.3.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Square Peg, Round Hole: First Nations Drinking Water Infrastructure and Federal Policies, Programs, and Processes

Abstract: Despite nearly a decade of targeted federal government efforts to provide potable water to First Nations communities in Canada, drinking water advisories and piped-water infrastructure gaps still persist. An indepth understanding of technical practitioners' perspectives and experiences with federal policies, programs, and processes (PPP) may provide unique insight into the challenges behind the issues. To meet this objective, we interviewed 16 First Nations technical staff within the geopolitical boundary of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
(7 reference statements)
0
13
0
Order By: Relevance
“…Among articles that focused on drinking water policy challenges, articles discussed the lack of legally enforceable Federal safe drinking water standards on reserves [91], along with the complicated policy framework currently in place [88]. Articles that focused on infrastructure challenges primarily discussed challenges with water treatment infrastructure, the lack of local operator training, and the lack of financial support, consistent with challenges reported in literature [88, 92].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Among articles that focused on drinking water policy challenges, articles discussed the lack of legally enforceable Federal safe drinking water standards on reserves [91], along with the complicated policy framework currently in place [88]. Articles that focused on infrastructure challenges primarily discussed challenges with water treatment infrastructure, the lack of local operator training, and the lack of financial support, consistent with challenges reported in literature [88, 92].…”
Section: Discussionmentioning
confidence: 77%
“…The lack of government funding available to address Indigenous water security challenges [82, 88, 89], along with the history of water-related government actions [82, 89], have been reported in peer-reviewed literature. While progress was made in improving safe drinking water provision in high risk communities [90], the emphasis on government responses surrounding inadequate funding and action, along with the persistence of drinking water issues [75], suggest a call for further government support and action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing safe drinking water continues to be a challenge for First Nations communities in Canada despite considerable financial investment from the Canadian federal government over the last decade (McCullough & Farahbakhsh, 2012). In Neegan Burnside Ltd.'s 2011 National Assessment of First Nations Water and Wastewater Systems, a project commissioned by the federal government, 807 water systems serving 560 First Nations communities were assessed.…”
Section: Insights and Opportunities: Challenges Of Canadian First Natmentioning
confidence: 99%
“…Although user fees are collected in these communities, operators still complain of inadequate funds for operation and maintenance, noting that Band Councils ask them to reduce costs or claim that the budget is in deficit, therefore restricting the flow of funds. McCullough and Farahbakhsh (2012) suggested that the 80:20 split in operation and maintenance costs does not reflect economic reality because many communities do not have income-generating activities that can support the collection of user-fees and, as a result, this funding divide sets the stage for two-tier service delivery-communities with higher incomes can afford to pay for more qualified operators and keep up with maintenance needs, in contrast to those whose incomes are lower and must cut salaries and corners in terms of operation and maintenance. Nevertheless, the collection of user fees alone does not seem to preclude two-tier service delivery in the Ontario communities interviewed.…”
Section: Job Satisfaction and Operator Retentionmentioning
confidence: 99%